(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Scholars of Samarkand origin also played an important role in the spread of Islam in the Indonesian archipelago in the XIV-XV centuries. One of these scholars is Malik Ibrahim Samarkandi. Sources say that he was originally from Samarkand and was the son of Mawlana Hussein Jumadil Kubro, known among the Indonesian people as Sheikh Jumadul Kubro or Jamoliddin Akbar al-Husseini. These two scholars belong to the circle of scholars of nine saints known as Wali songo, who made a great contribution to the spread of Islam in the regions of Southeast Asia. According to sources, Ibrahim Samarkandi was one of the first to establish a religious madrasa-school in Indonesia to teach Islamic teachings. Today, there are universities and institutes named after him in the Republic of Indonesia. According to researchers, Mawlana Jumadil Kubro first came to Java with his two sons, Ibrahim and Ishaq. They then split up and spread in different directions in order to spread Islam. According to sources, Jumadil Kubro remained on the island of Java, Ibrahim Samarkandi left for Champa (now Vietnam), and Mawlana Ishaq left for Pasai, the northern part of Sumatra. Information about their later lives varies, with some claiming that Ibrahim Samarkandi practiced medicine and trade, taught local farmers the culture of farming, married the daughter of one of the local rulers, had two children, and then left his family to return to Java. He is said to have spent the rest of his life in a village now known as Gresik, and to have died in 1419. Today, its mausoleum is one of the most important pilgrimage sites for the locals. Sources say that Ibrahim Samarkandi caused many locals to convert to Islam. The main reason for this is that as a result of his trade activities he met many aristocrats, from whom he received great help in spreading Islam. This article examines the personality, genealogy and life of Malik Ibrahim Samarkandi from a scientific point of view. In addition, the importance of Ibrahim Samarkandi in the early stages of the spread of Islam in the Indonesian archipelago is studied. The research also reveals the specific connections of Islam in the XIV-XV centuries in the Samarkand region and the island of Jawa.